Educational innovation for Industry 4.0: an exploration of integrated work-based learning's contribution - Agus Prohimi, Afwan Hariri; Syihabudhin, S.E.; Juariyah, Lohana; Bidin, Rosmiza; Gunawan, Ari; Syafruddin, Afis Baghiz (Universidade Nove de Julho, 2024)
Purpose: The purpose of this research is to explore the role of integrated work-based learning in preparing students to meet the challenges of the Industry 4.0 work environment. It aims to investigate how incorporating work-based learning elements into the educational curriculum can enhance students' readiness for the dynamic and technology-driven landscape of Industry 4.0. Theoretical framework: This study is grounded in the theoretical framework of constructivism and experiential learning. Constructivism emphasizes active learning and the development of meaningful understanding through real-world experiences. Experiential learning theories, particularly Kolb's model, inform the research, highlighting the importance of concrete experiences, reflective observation, abstract conceptualization, and active experimentation in the learning process. Method/design/approach: A mixed-methods approach will be employed for this research. Quantitative data will be collected through surveys and assessments to measure the impact of integrated work-based learning on students' technical and soft skills. Qualitative data will be gathered through interviews and focus groups to explore students' perceptions and experiences. Results and conclusion: The results will provide insights into the effectiveness of integrated work-based learning in enhancing students' technical and soft skills. It will reveal the impact on their readiness for Industry 4.0 careers, as well as their ability to navigate the complexities of the modern workplace. Research implications: This research holds implications for educational institutions, policymakers, and industry stakeholders. It underscores the need to integrate work-based learning elements into curricula to better prepare students for Industry 4.0 careers. The findings will inform the development of strategies that enhance students' workforce readiness. Originality/value: This research contributes to the growing body of literature on work-based learning and its role in Industry 4.0 preparedness. It provides original insights into the effectiveness of integrated work-based learning programs, their impact on students, and their value in addressing the demands of the rapidly evolving work environment.